Knowledge, Attitude and Practice of Hospital Pharmacists in Central China Towards Adverse Drug Reaction Reporting: A Multicenter Cross‐Sectional Study - Hu, Wen; Tao, Yun; Lu, Yun; Gao, Suyu; Wang, Xuanxuan; Li, Wenjing; Jiang, Qiaoli; Lin, Likai; Sun, Feng; Cheng, Hong (Frontiers in Pharmacology, 2022)
Background: Healthcare professionals’ knowledge and attitudes towards adverse drug reactions (ADRs) and ADR reporting play a significant role in pharmacovigilance. This study aims to investigate the gap between knowledge and practice in ADR reporting among hospital pharmacists. Methods: This study is a multi-center, cross-sectional study based on a questionnaire survey. A semi-structured questionnaire was developed including knowledge, attitudes, and practices (KAP) towards ADR reporting. From October to November 2021, questionnaires were filled out on the internet by hospital pharmacists from a central province of China. The data analysis used a one-way ANOVA to analyze the differences between the pharmacist's characteristics and knowledge and attitude, respectively. The ordinal logistic regression method was used to analyze the predictors of KAP. Results: A total of 1,026 valid questionnaires from 512 medical institutions were collected. It was found that 88.8% of participants have a clear understanding of the ADR definition, while 59.6% of them have misunderstandings about the reporting time of new and serious adverse reactions. Most pharmacists showed positive attitudes towards ADR reporting. Higher education background, higher professional title, attending training, and clinical pharmacist resulted in higher knowledge scores. Higher education background, shorter working years, attending training, and from non-tertiary hospital related to higher attitude scores. In terms of practice, age, hospital type, working years, training, and pharmacist type all have significant associations with practice scores. Pharmacists’ knowledge score and practice score were significant predictors of practice score with OR being 1.19 (95% CI: 1.06, 1.33) and 1.04 (95% CI: 1.005, 1.07). Conclusion: Although most hospital pharmacists showed positive attitudes towards ADR reporting, their knowledge and practice were still insufficient. Hospital pharmacists’ knowledge is associated with their practice towards ADR reporting. The training had a significant impact on the pharmacist’s knowledge, attitude, and practice.